Cautious Exploitation: Learning and Search in Problems of Evaluation and Discovery - Levinthal, Daniel A.; Schliesmann, Daniel (Organization Science, 2025)
Underlying the macrophenomenon of organizational search lie two central mechanisms: belief updating and explicit strategies of exploration/exploitation. We find that slow learning with respect to belief updating, in conjunction with a strategy of exploration/exploitation heavily tilted toward exploitation, leads to an effective process of organizational adaptation in a wide variety of settings. This joint search strategy can be thought of as “cautious exploitation.” Belief updating proves to be a more effective catalyst to search, facilitating both the process of discovery of alternatives and persistence in favorable alternatives, than an explicit strategy of exploration. However, it is important to consider the boundary conditions around this finding. Problems of search differ in important respects: from settings that are primarily problems of discovery where the critical challenge is identifying a promising alternative, but its promise is self-evident once identified, to problems of evaluation where assessing the merit of alternatives that are identified is itself a challenge. We find that our conventional wisdom about the role of explicit strategies of exploration holds in settings that are primarily problems of discovery. However, when the evaluation of alternatives is problematic and assessed through experience with a given alternative, we find that the macrophenomenon of effective organizational search is best realized with slow rates of belief updating in conjunction with an explicit strategy of exploration/exploitation that is tilted to be highly exploitative. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.17538 .